PELAYANAN PEMERINTAH DESA DALAM PEMBERIAN SURAT KETERANGAN TANAH DI DESA SUNGAI RISAP MENSIKU BERSATU KECAMATAN BINJAI HULU KABUPATEN SINTANG - Robert Hoffman (Universitas Kapuas Sintang, 2018)
The Sintang Regency Government as one of the regency governments in Indonesia in terms of granting land rights certificates (SKT) has submitted its affairs to the village, including the Sungai Risap Mensiku Bersatu Village, Binjai Hulu District. Therefore, the Village Head of Sungai Risap Mensiku Bersatu, as the leader of the implementation of the village administration together with all the village apparatus is required to provide services to the community in terms of granting land title (SKT). The type of research used is descriptive research with a qualitative approach. The subject of this research was the Village Head and the Community of Sungai Risap Mensiku Bersatu Community, Binjai Hulu District. The results of this study indicate that the service of the village government in the granting of land certificates in the River Village Risap Mensiku Bersatu, Binjai Hulu Subdistrict, Sintang Regency is carried out with service procedures, time of completion, apparatus resources and facilities and infrastructure. The conclusions from the results of this study that the service of the village government in the provision of land certificates in Sungai Risap Mensiku Bersatu Village, Binjai Hulu Subdistrict, Sintang Regency was carried out by: service procedures: first the people who would take care of the SKT came and took the SKT blank, second, filled out and completed the identity themselves according to the No Population Card (KTP), and thirdly, the staff from the village apparatus will go down to examine the field in the presence of witnesses to land boundaries; Completion time : SKT arrangement is a maximum of 30 to 40 minutes to complete the file and 1-2 days to complete the file starting from submission until the issuance of the SKT file; Apparatus resources: have competencies that are appropriate in their fields; and facilities and infrastructure: service rooms and typewriters. From the results of the conclusions, the researcher suggests that Mensiku Bersatu River Village Office, United Binjai Hulu District in Sintang District in carrying out its main tasks and functions prioritizes the public service management system that must have standard operating procedures (SOP) and have information media for the community, so the community easily knows the mechanism for taking care of the SKT and the length of time to complete it.